2015
DOI: 10.1177/0963662515598249
|View full text |Cite
|
Sign up to set email alerts
|

The ‘credibility paradox’ in China’s science communication: Views from scientific practitioners

Abstract: In contrast to increasing debates on China’s rising status as a global scientific power, issues of China’s science communication remain under-explored. Based on 21 in-depth interviews in three cities, this article examines Chinese scientists’ accounts of the entangled web of influence which conditions the process of how scientific knowledge achieves (or fails to achieve) its civic authority. A main finding of this study is a ‘credibility paradox’ as a result of the over-politicisation of science and science co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 27 publications
1
21
0
Order By: Relevance
“…In her studies, Smith (2016) demonstrated scientists' willingness for public engagement on Twitter, despite their apparent claims that were based on the deficit model, and J. Y. Zhang (2015) displayed Chinese scientists' voluntary practice of science communication despite political control. Our study has paralleled these earlier findings with more evidences.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In her studies, Smith (2016) demonstrated scientists' willingness for public engagement on Twitter, despite their apparent claims that were based on the deficit model, and J. Y. Zhang (2015) displayed Chinese scientists' voluntary practice of science communication despite political control. Our study has paralleled these earlier findings with more evidences.…”
Section: Discussionmentioning
confidence: 99%
“…Second, social media has changed the transmission and control of information dramatically in China (Tu, 2016), but what impact has it exerted on State-dominated science communication in the country (Jia & Liu, 2014; J. Y. Zhang, 2015)? State-dominated science communication, which is sometimes equivalent to propaganda, is featured by publicizing scientific achievements and boasting of their political implications and the advantages of socialism, and highlighting national pride (Jia & Liu, 2009;Jia & Liu, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Science popularization refers to a kind of activity or tool, rather than to a theory, and is the main concept used in China, according to Xu et al (2015). In the literature, the focus has been on notions such as scientific popularization, scientific literacy, popular science publishing and science communication (Jia and Liu, 2014;Wu and Qiu, 2013;Xu et al, 2015;Zhang, 2015). Public engagement was seen as influencing decision-making and, more broadly, as influencing engagement in science communication activities, in which large groups were actively participating.…”
Section: Rri At the Conceptual Levelmentioning
confidence: 99%
“…In some cases, inattentiveness to research activities outside centralized funding schemes may create an adverse situation in which 'the bad drives out the good'. For example, during my fieldwork as Expert Consultant for the Ministry of Science commissioned project, 'Ethical Issues and Governing Strategies in Scientific Research' in 2014 [48], one stem cell scientist at Tongji University complained to us that as the then MOH had prohibited unauthorized stem cell research, his state-funded project was effectively suspended until further clarity from the government. In the meantime, rival researchers working in the commercial sector forged ahead, for their careers and future funding were independent from the state system.…”
Section: Emerging Blind Spots In 'Soft Centralization'mentioning
confidence: 99%